2013
DOI: 10.1155/2013/549705
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Kenaf Seed Oils from Supercritical Carbon Dioxide Fluid Extraction towards Human Colorectal Cancer (HT29) Cell Lines

Abstract: Kenaf (Hibiscus cannabinus) from the family Malvaceae, is a valuable fiber plant native to India and Africa and is currently planted as the fourth commercial crop in Malaysia. Kenaf seed oil contains alpha-linolenic acid, phytosterol such as β-sitosterol, vitamin E, and other antioxidants with chemopreventive properties. Kenaf seeds oil (KSO) was from supercritical carbon dioxide extraction fluid (SFE) at 9 different permutations of parameters based on range of pressures from 200 to 600 bars and temperature fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…The functional groups in phenolic and flavonoid compounds present in the kenaf plant exhibit antioxidant properties and inhibit the angiotensin I-converting enzyme and lipid peroxidation (Jin et al 2013;Ghafar et al 2013). In this study, the TPC and TFC of the kenaf leaf and flower were promising.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The functional groups in phenolic and flavonoid compounds present in the kenaf plant exhibit antioxidant properties and inhibit the angiotensin I-converting enzyme and lipid peroxidation (Jin et al 2013;Ghafar et al 2013). In this study, the TPC and TFC of the kenaf leaf and flower were promising.…”
Section: Discussionmentioning
confidence: 61%
“…Hydrocarbon compounds have been shown to exhibit antimicrobial activity (Kobaisy et al 2001;Ebije et al 2014). Kenaf seeds oil is used for margarine, and it is thus safe for human and animals (Mohamed et al 1995;Ghafar et al 2012;Alexopoulou et al 2013;Ghafar et al 2013;Ryu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, to overcome the toxicity and safety issues modern phyto-extraction techniques like sonication, soxhlet, supercritical carbon dioxide fluid extraction (SFE) etc. have been extensively utilized for extracting kenaf seed oil (Wang and Weller, 2006;Chan and Ismail, 2009;Foo et al, 2011;Mariod et al, 2011;Yazan et al, 2011;Ghafar et al, 2013;Ng et al, 2013). In recent time, soxhlet and SFE methods have extensively been used for extraction of kenaf seed oil with enriched fatty acids and antioxidants (Chan and Ismail, 2009;Nyam et al, 2010;Mariod et al, 2011;Ng et al, 2013).…”
Section: Extraction Of Kenaf and Roselle Seed Oilmentioning
confidence: 99%
“…Antioxidant capacities Chew, 2003;Amin and Mukhrizah, 2006;Amin and Chew, 2006;Bako et al, 2009;Chan and Ismail, 2009;Mohd-Esa et al, 2010;Nyam et al, 2012;Yusri et al, 2012;Wong et al, 2014a 2. Antimicrobial effects Gangrade et al, 1979;Nwaiwu et al, 2012 3. Lactating activity Gaya et al, 2009 4. Anti-inflammatory and analgesic activities Ali et al, 2014 5. Functional additives in fermented foods Agbobatinkpo et al, 2011Agbobatinkpo et al, , 2013 Used to relieve pain in urination and indigestion Morton, 1987 7. Residue from seeds oil extraction used as animal feed Al-Wandawi et al, 1984;Morton, 1987;Mukhtar, 2007;Elamin et al, 2012 8. Cytotoxic activities and chemopreventive properties Yazan et al, 2011;Ghafar et al, 2012Ghafar et al, ,2013Wong et al, 2014b 9. Anti-leukemic properties Warner et al, 1969 (unpublished data);Foo et al, 2011 10. Hydrolytic enzyme activity Amma et al, 1977 11.…”
Section: Sr Nomentioning
confidence: 99%
“…Thus, the supercritical carbon dioxide extraction technology has been studied extensively as an alternative to conventional methods of oil extraction since it is nontoxic, nonflammable and easily separated from the extract (Pang et al, 2015). SC extraction has been widely applied to extract oil from plant seeds, such as canola seed (Pederssetti et al, 2011), kenaf seed (Abd Ghafar et al, 2013), Phaleria macrocarpa seed (Azmir et al, 2014) and okra seed (Dong et al, 2014). In one study, where peony seed oil was mainly extracted using the screw press and solvent methods, it was demonstrated that extraction at atmospheric pressure resulted in the absence of linolenic acid, while extraction under 350 MPa exhibited the highest fatty acid number and fat acidity among all the oils .…”
Section: Introductionmentioning
confidence: 99%